2019
DOI: 10.21744/irjmis.v6n4.640
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure as a mediation variable: Profitability and liquidity on company value in real estate companies in Indonesia stock exchange

Abstract: The purpose of this study is to determine the effect of variable profitability, liquidity, and capital structure on the firm value in real estate companies listed on the Indonesia Stock Exchange (IDX). The population of this study is a real estate company listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The method of determining the sample in this study used a purposive sampling method, with several predetermined criteria, then the number of selected samples was 26 companies. Data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
4
21
0
3
Order By: Relevance
“…Indirectly the company's condition that experienced high asset growth rate will reflect the company needs more funding for the cost of acquisition, maintenance costs, and operational costs. Therefore, the increase in assets followed by the increase in operational is able to increase the outside trust of the company, hence the proportion of debt is greater than the capital itself [16]. H2 : Asset growth has an influence on capital structure.…”
Section: Asset Growth To Capital Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Indirectly the company's condition that experienced high asset growth rate will reflect the company needs more funding for the cost of acquisition, maintenance costs, and operational costs. Therefore, the increase in assets followed by the increase in operational is able to increase the outside trust of the company, hence the proportion of debt is greater than the capital itself [16]. H2 : Asset growth has an influence on capital structure.…”
Section: Asset Growth To Capital Structurementioning
confidence: 99%
“…Statted that empirically the relationship of cash flow volatility with a weak capital structure, but the results of his research showed a different thing that is volatility of cash flows is an important determinant of the company's debt ratio and the use of debt with different maturity. In theory cash flow volatility affects the structure of capital [16].…”
Section: Cash Flows Volatility To Capital Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobb-Douglas theory which states that capital affects production output. This shows the higher capital will be able to increase production output, this is because in the production process requires costs that are used for labor and the purchase of raw materials and equipment (Sulistiana, 2013;Nneka et al, 2016;Putra & Sedana, 2019). The number of workers is very influential on income, if the work user increases, the results of the production of goods will increase and affect the increase in income of the entrepreneur, and vice versa a Udayana University, Denpasar, Indonesia b Udayana University, Denpasar, Indonesia when the labor used decreases or is small, then the production results obtained are few or the workmanship is not timely, resulting in entrepreneur income will decrease.…”
Section: Introductionmentioning
confidence: 99%
“…There are three techniques for a company to increase equity that are: private placement, public offer, dan rights issue (Martino & Busatto, 2018;Pratama & Rahyuda, 2019). The rights issue is a more profitable choice for a company to gain additional equity compared to bank loans and the issuance of debt securities (Sihaloho & Handayani, 2018;Putra & Sedana, 2019). Balachandran et al, (2017), stated that a company spends more cost to do public placement rather than a rights issue.…”
Section: Introductionmentioning
confidence: 99%